Rural tourism: the content, features and types - Yuriy Onoyko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Despite the active development of rural tourism in Ukraine, this phenomenon is still under scientific study nowadays, which has been manifested by the uncertainty of the key terms; by the lack of clear boundaries, which can separate this type of tourism from other types of tourism activities; by debates about the essence and types of rural tourism. After analyzing the available information the author offers own generalized definition of rural tourism. Rural tourism is a specific entertaining and educational type of tourism, which is based on the tourists’ stay within rural estates, for the purpose of studying the life of peasants, acquaintance with traditional crafts, culture and customs of the rural population, knowledge of the natural, historical and cultural sites in and around rural settlements.